'You have hands, make use of them!' Child labour in Artisanal and Small‐scale Mining in Tanzania. (20th September 2016) - Potter, Cuz; Lupilya, Alexander Constantine
Abstract: This paper examines child labour in artisanal mining through ethnographic research in Tanzania. The poverty hypothesis argues that households send children to work to bolster household income. The sociocultural approach suggests that child mining offers valuable vocational training. This paper builds on a growing literature that complicates these approaches' straightforward claims by illustrating how household fragmentation is generated through the encounter of traditional cultural practices with mining's culture of consumption. This encounter exacerbates household fragmentation, which in turn increases child poverty and labour. These findings suggest that policy interventions should also address these mediating factors rather than poverty per se . Copyright © 2016 John Wiley & Sons, Ltd.